2018
DOI: 10.1002/app.47009
|View full text |Cite
|
Sign up to set email alerts
|

Transport properties of blended sulfonated poly(styrene‐isobutylene‐styrene) and isopropyl phosphate membranes

Abstract: This work discusses the effect of isopropyl phosphate (IP) on the transport properties of sulfonated poly(styrene-isobutylene-styrene) (SO 3 H SIBS) as membranes for direct methanol fuel cell (DMFC) and chemical and biological protective clothing (CBPC) applications. The properties were determined as a function of SIBS sulfonation level (i.e., 24, 34, 49, and 84 mol %) and IP loading (i.e., 1, 3, 5, 11, and 15 wt %). A comprehensive material characterization study (e.g., FTIR, TGA, AFM, and SAXS) was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 56 publications
(63 reference statements)
1
11
0
Order By: Relevance
“…For stability measurements, small samples of membranes were dried at 60°C for 24 h, weighted and then immersed in 10 ml of Fenton's reagent (4 ppm Fe [SO 4 ] 2 ·7H 2 O in 3 wt% H 2 O 2 aqueous solution) at 60°C for 1 h. After that, samples were cleaned with deionized water, dried at 60°C for 48 h, and then their remaining weights were recorded. Stability was evaluated by calculation of the residual weight percentage (RW) using Equation 34 : italicRW0.25em()italicwt%=WitalicremainingWitalicinitial×100 where W initial and W remaining represent the initial and remaining weights of the membranes, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For stability measurements, small samples of membranes were dried at 60°C for 24 h, weighted and then immersed in 10 ml of Fenton's reagent (4 ppm Fe [SO 4 ] 2 ·7H 2 O in 3 wt% H 2 O 2 aqueous solution) at 60°C for 1 h. After that, samples were cleaned with deionized water, dried at 60°C for 48 h, and then their remaining weights were recorded. Stability was evaluated by calculation of the residual weight percentage (RW) using Equation 34 : italicRW0.25em()italicwt%=WitalicremainingWitalicinitial×100 where W initial and W remaining represent the initial and remaining weights of the membranes, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…It can be observed from Figure 1(a) that sulfonated membrane spectrums indicate four characteristic peaks at 1006, 1034, 1125, and 1158 cm −1 , which confirms the successful incorporation of sulfonic ( SO 3 H) groups into the polymer structure. 3,34 The peaks at 1006 and 1034 cm −1 are associated with the symmetric stretching vibration of the O S O bond, while the peaks at 1125 and 1158 cm −1 are related to the asymmetric stretching vibration of the O S O bond. 33 In addition, a band at 834 cm −1 is attributed to para-substitution of SO 3 H groups in the aromatic rings.…”
Section: Fourier Transform Infrared Spectroscopymentioning
confidence: 99%
“…Their work also suggested that the addition of isopropyl groups enforced the hydrophobic domains to reduce the methanol transport through the membrane. 27 In a study performed by Ahn et al blends made from cross-linked sulfonated poly(arylene ether)s and triazole containing PAES achieved proton conductivities over 0.12 S cm À1 at 80 C (95% relative humidity), without sacrificing the stability of the membranes. 28 Also, Haragirimana et al studied the effect of creating a four polymer composite membranes made of PAES with sulfonation levels 20%, 30%, 40%, and 50%, variating the ratio of the polymer.…”
Section: Introductionmentioning
confidence: 99%
“…The self-assembly of a PEM upon solvation can form a permselective network containing nanoscale hydrophilic channels. Typical examples of such selective permeable membranes are sulfonated poly(styrene-isobutylene-styrene) (SIBS), triblock copolymer, perfluorinated ionomers, and polystyrene sulfonic acid (PSSA) [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. However, sulfonated SIBS has poor selectivity between 0.7 and 35 [ 19 ], Nafion is too expensive for chemical protective clothing usage ($1600 m −2 for Nafion 117) [ 20 ], and polystyrene sulfonic acid has a poor mechanical performance [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, sulfonated SIBS has poor selectivity between 0.7 and 35 [ 19 ], Nafion is too expensive for chemical protective clothing usage ($1600 m −2 for Nafion 117) [ 20 ], and polystyrene sulfonic acid has a poor mechanical performance [ 14 ]. As for the selectivity of the membrane, Suleiman et al systematically studied the water/DMMP selectivity of a SIBS-based ion exchange membrane under different degrees of sulfonation [ 18 , 19 ]. By using classical molecular dynamics simulations, Neimark et al explored the nanoscale segregation and diffusion of water and nerve gas simulant DMMP in sulfonated polystyrene (sPS) at different sulfonation and hydration levels.…”
Section: Introductionmentioning
confidence: 99%